Revision of the Apocephalus analis group of ant-decapitating flies (Diptera: Phoridae) - Brown, Brian V. (Zootaxa, 2014)
The species of the mostly Neotropical Region Apocephalus analis group are revised, and found to comprise 21 species, 19 of which are new to science: A. bilineatus, A. euryacanthus, A. holdenae, A. mexacanthus, A. paracanthus, and A. rectisetus in the newly recognized A. comatus series, and the following unclassified species: A. amacayacuensis, A. amati, A. amenti, A. amorimi, A. camarae, A. criniventris, A. gonzalezae, A. marinhoi, A. papei, A. pittadearaujoi, A. riccardae, A. strazhnikae, and A. xavierfilhoi. Little is known of the natural history of this group, other than that the two previously known species, A. analis Borgmeier and A. comatus Borgmeier, were collected with the army ant Labidus coecus (Latreille).